Desenvolvimento de reator UASB com duplo estágio de coleta de biogás (DECB), aplicado ao tratamento de esgoto sanitário, objetivando o controle da escuma e a granulação do lodo - Jackson de Oliveira Pereira (2012)
This thesis aimed to evaluate the use of a modified version of the UASB reactor, designed with two biogas collectors, called UASB/DSBC (UASB reactor with double stage biogas collection), on scum control and sludge granulation. Besides a new biogas collector, introduced on 1 m from the bottom of the reactor (1th stage biogas collection), the modified reactor is also designed with holes in three-phase separator (2nd stage biogas collection). Regarding scum accumulation, the experiments were carried out in two pilot-scale UASB reactors, one being the modified UASB reactor (UASB/ DSBC), and the other a conventional UASB reactor, both with total volume of 343 L and 4 m high, treating raw sewage. The reactors were operated in four distinct phases with different operating conditions of flow, HRT, reactor configuration (holes in the biogas collector, open or closed) and sludge discharge strategies, to enable monitoring of the main parameters of interest, like the scum, the quality of effluent and sludge granulation. The results obtained in tracer studies confirmed the best hydrodynamic mixing conditions in the modified reactor and the occurrence of air-lift mechanism. The results of scum accumulation inside the three-phase separator showed that the modified reactor had effective control when operated with hole opened. The reduction in mass accumulation of scum TS, TVS and COD was greater than 70 %, 67 % and 65 % for HRT of 7 h, and 83 %, 84 % and 81 % for HRT of 5 h. Despite these good results, the modified reactor showed lower performance of the removal of organic matter from the liquid phase. When the reactor operated with holes closed (HRT of 7 h), the mechanism of biological degradation did not promote the control of scum inside the three-phase separator. Finally, the evaluation of the selection of biomass granules with higher activity (for HRT of 7 h and reactors operated without sludge discharges) revealed that after the 40th days from inoculation, the modified sludge reactor showed a greater production of extracellular- carbohydrate (146 mg/gTVS) than the conventional reactor (97 mg/gSTV). The activity in this same period was the 0.13 g COD-CH4/gTVS.d in the modified reactor and only 0.07 gCOD-CH4/gTVS.d on the conventional reactor. These results showed that the modified reactor was able to promote granulation and select a biomass of greater activity in the shortest period of time. Thus, it was concluded that the modified reactor can promote the effective control of scum inside the three-phase separator, as well as optimize the time to develop a more active granular biomass. However, further adjustments are necessary for its complete development.